Evaluation of udder health and body condition score in saanen and shami-jamnapari crossbred - Che Mat, Norfadhilah (2017)
Morphological of udder and body condition score are very critical in dairy animals as they could be a factor that cause the production of milk decreased. This study was conducted to evaluate the udder conformation and the body condition score of lactating Saanen and Shami-Jamnapari crossbreds does in one dairy goat farm. In addition, the study also evaluated the changes in the conformation traits of the udder and the body conformation score for the two breed types at different lactation stages. A total of 20 does from two breed types of lactating goats were used as the experimental material in the study, namely 10 Saanen goats and 10 Shami-Jamnapari crossbreds. The study has been conducted at Gmilk Farm in Nilai, Negeri Sembilan. Udder health is assessed by using conformation traits of the udder and the teats, as well as structural abnormality and asymmetry. Udder was evaluated by observation using back and side views. The morphology traits measured were udder depth (UD), udder circumference (UC), udder width (UW), teat length (TL), teat width (TW), teat circumference (TC), and distance between teats (DBT). Body condition scoring is done by manual palpation around the vertebrae in the lumbar and sternal regions. A score on the scale of 1 - 5 are assigned to each animal. The measurement and scoring is done two hours before evening milking session. The result indicated that there was no interaction between breed and lactation number for udder and teat measurement traits. There were generally no significant differences (P>0.05) in udder and teat measurement traits between primiparous and multiparous does. However, there were significant differences (P<0.05) in udder width and udder circumference between the breeds during all four time of lactation studied. In addition, during the third and fourth visit there was significant difference (P<0.05) between breeds for udder depth as well. There was no significant differences in body condition score (BCS) between the two breeds except for the fourth visit. It was concluded that the BCS between lactating Saanen and Shami-Jamnapari in the farm were similar. However, the morphology of the udder between the two breeds were different. The lactation number had no effect on the udder morphology.